Association between sensitivity to thyroid hormone indices and the risk of osteoarthritis: an NHANES study - Shuai Chen; Xiaohe Sun; Guowei Zhou; Jie Jin; Zhiwei Li (European Journal of Medical Research, 2022)
Abstract Objectives Thyroid hormones play an instrumental role in chondrogenic differentiation and matrix maturation. However, studies investigating the relationship between thyroid function and the risk of osteoarthritis (OA) remain scarce. This study was designed to investigate the correlation between thyroid status and OA from a novel perspective of sensitivity to thyroid hormones. Methods The study included 8478 people from the National Health and Nutrition Examination Survey (NHANES) 2007–2010. The sensitivity to thyroid hormone indices included Thyrotroph Thyroxine Resistance Index (TT4RI), Thyroid-stimulating hormone (TSHI), Thyroid Feedback Quantile-based Index (TFQI), and Free Triiodothyronine /Free thyroxine (FT3/FT4), which were calculated based on serum free triiodothyronine (FT3), free thyroxine (FT4), and thyroid stimulating hormone (TSH). Considering the complex survey design and sample weights, we employed multivariate linear regression models and stratified analysis to evaluate the correlation between sensitivity to thyroid hormone indices and OA. Results Study results indicated that participants with OA had elevated TT4RI, TSHI, and TFQI levels, and lower FT3/FT4 levels compared to those with non-arthritis. After adjusting for other covariates, FT3/FT4 was negatively associated with the risk of OA (OR = 1.162, 95%CI 1.048–1.478, P = 0.021); (OR = 1.261, 95%CI 1.078–1.623, P = 0.042). In subgroup analyses stratified by gender and BMI, participants with OA had higher TFQI levels compared to those without OA in both genders. (OR = 1.491, 95%CI 1.070–2.077, P = 0.018); (OR = 2.548, 95%CI 1.929–3.365, P < 0.001). The higher TFQI levels were consistently associated with the increased prevalence of OA in the BMI (< 18.5 kg/m2) group after adjusting for different covariates, but not in other BMI groups. In, addition, TFQI performed better than FT3/FT4, TSHI, and TT4RI on ROC analyses for OA prediction. Conclusions The levels of FT3/FT4, TSHI, TT4RI, and TFQI are strongly associated with the prevalence of OA, which illustrates the complex correlation between the thyroid system and chondrogenic differentiation. TFQI may be used as a helpful indicator to predict OA and provide novel ideas for the evaluation and treatment of OA.